The predictive ability of ABSI compared to BMI for mortality and frailty among older adults - Shafran, Itamar; Krakauer, Nir Y.; Krakauer, Jesse C.; Goshen, Abigail; Gerber, Yariv (Frontiers in Nutrition, 2024)
To study the utility of A Body Shape Index (ABSI) alongside body mass index (BMI) to predict mortality and frailty in an aging community population.: Participants (n=1,580) were drawn from the first Israeli national health and nutrition survey of older adults ("Mabat Zahav") conducted from 2005-2006, constituting adults aged ≥65 years. Socio-demographic, clinical, behavioral, and psychosocial data were collected. Baseline weight, height, and waist circumference (WC) were measured and expressed as the allometric indices BMI (kg/m 2 ) and ABSI, a BMI-independent measure of abdominal obesity [WC/(BMI 2/3 *m 1/2 )]. Mortality follow-up lasted through 2019. Frailty was assessed in 2017-2019 by the Fried Biological Phenotype in a sub-cohort of 554 survivors. Cox and logistic regression models assessed associations of BMI and ABSI with mortality and frailty.Results: At baseline, mean [SD] age was 74.5 [6.1] years, and 52.4% were women. The correlation between BMI and WC Z scores was 0.71, reduced to -0.11 for BMI and ABSI. Over a median follow-up of 13 years, 757 deaths occurred. The multivariable-adjusted hazard ratios (95% CIs) for mortality per standard deviation increase in BMI and ABSI were 1.07 (0.99;1.17) and 1.13 (1.05;1.21), respectively. Among participants assessed for frailty, 77 (14%) met the frailty criteria. After multivariable adjustment, the odds ratios (95% CIs) for frailty were 0.83 (0.69-1.01) for BMI and 1.55 (1.34-1.79) for ABSI.Discussion: In a nationwide cohort of older adults, ABSI was independently associated with mortality risk. Furthermore, ABSI, but not BMI, was a strong predictor of frailty.